2019
DOI: 10.1002/cnma.201900348
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Metal Ion Counter Diffusion in Confined Spaces for In Situ Growth of Mixed Metal MOF Membranes for Gas Separation

Abstract: The development of facile, versatile strategies for the fabrication of mixed component metal‐organic framework (MOF) membranes is highly desired, but still very challenging due to the difficulty in controlling crystal growth rates of every single component in a specific confined space. It is difficult to adjust the formation of multicomponent MOF membrane in a controlled manner using conventional approaches such as secondary growth methods. Herein, we present a facile strategy that prepares the mixed metal zeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The H 2 /CO 2 separation performance was compared with that of previous membrane materials, including MOFs, zeolites, and two‐dimensional (2D) materials (Figure 3e and Table S2) [33–70] . Ideal separation performance (marked with a black star) of the ZIF‐8/GNR/alumina(300) membrane surpasses the upper bounds of reported polycrystalline MOF membrane performance and is located in the state art range of 2D materials‐based membranes (e.g.…”
Section: Resultsmentioning
confidence: 96%
“…The H 2 /CO 2 separation performance was compared with that of previous membrane materials, including MOFs, zeolites, and two‐dimensional (2D) materials (Figure 3e and Table S2) [33–70] . Ideal separation performance (marked with a black star) of the ZIF‐8/GNR/alumina(300) membrane surpasses the upper bounds of reported polycrystalline MOF membrane performance and is located in the state art range of 2D materials‐based membranes (e.g.…”
Section: Resultsmentioning
confidence: 96%
“…The contra-diffusion synthetic protocol, which is featured with physical segregation of two precursor solutions containing metal ions and organic ligands, enabled concentration gradient-driven metal–ligand self-assembly, offering significant potential for the fabrication of ultrathin MOF membranes. This technique has garnered attention for its “self-regulating” capability, offering significant advantage in terms of ultrathin MOF membrane preparation. Wang et al pioneered the preparation of continuous ZIF-8 membrane using contra-diffusion technique . Recently, a confined counterdiffusion strategy was further developed to enable epitaxial growth of (111)-oriented 165 nm thick UiO-66 membranes .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have investigated the structure, , self-diffusion of ions, , and external force regulation , of confined ILs. Dong et al found that the migration of confined ILs in GO and MoS 2 membranes is different due to the discrepancy in ion interactions and diffusion.…”
Section: Introductionmentioning
confidence: 99%